2011
DOI: 10.1111/j.2044-835x.2011.02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Twelve‐month‐olds’ comprehension and production of pointing

Abstract: This study explored whether infants aged 12 months already recognize the communicative function of pointing gestures. Infants participated in a task requiring them to comprehend an adult's informative pointing gesture to the location of a hidden toy. They mostly succeeded in this task, which required them to infer that the adult was attempting to direct their attention to a location for a reason -because she wanted them to know that a toy was hidden there. Many of the infants also reversed roles and produced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(139 citation statements)
references
References 60 publications
4
130
1
4
Order By: Relevance
“…This tendency to trust some informants more than others is called ''selective trust.'' Human infants begin to understand and produce pointing at an early stage in their first year of life (Behne et al 2012). Pointing is such a conventional communicative gesture that young children have difficulty interpreting it in a novel, unconventional way.…”
Section: Introductionmentioning
confidence: 99%
“…This tendency to trust some informants more than others is called ''selective trust.'' Human infants begin to understand and produce pointing at an early stage in their first year of life (Behne et al 2012). Pointing is such a conventional communicative gesture that young children have difficulty interpreting it in a novel, unconventional way.…”
Section: Introductionmentioning
confidence: 99%
“…In one study [24], an experimenter pointed to one of two boxes, each containing a hidden toy, to request it from infants. Seventeen-montholds had no problem inferring that the point to the opaque box referred to the object inside (and not to the box itself; for similar results with 12-month-olds, see [25]). However, when the objects were swapped unbeknownst to the experimenter, and she then pointed to a box, infants apparently inferred the object she had in mind, namely the one that was now in the other box, and offered that object.…”
Section: (A) Comprehensionmentioning
confidence: 68%
“…By 1 year of age, infants begin pointing to absent, or experientially defined, referents making it clear that they understand that pointing is not simply a cue for attracting another's attention to a specific object, but instead is a means to orient them mentally to some shared representation. Also, infants begin to show comprehension of pointing, which requires more than merely following the direction of a point; infants search for invisibly displaced objects in locations that are specified by an adult's point, and search even longer when the object is not found at the pointed location (Behne, Liszkowski, Carpenter, & Tomasello, 2012;Gliga & Csibra, 2009). An especially compelling example of how infants comprehend pointing in terms of a shared understanding was reported by Liebal, Behne, Carpenter, and Tomasello (2009) who showed that 14-and 18-month-old infants interpreted an adult's pointing gesture differently depending on whether or not this individual had been involved with the infant in a previous activity.…”
Section: Point Following Versus Point Comprehensionmentioning
confidence: 97%